Plasma iron in newborn - Ramos Ramírez, José (1958)
Since he began studying the plasma iron have been countless jobs that have been made about it, but few in the world literature, which refer to the study of iron in the plasma of newborns and their evolution in the first days of life, in which, as is known, rapid changes are taking place in the blood picture, the detailed aspects are found in the work of C. Reynafarje H, E. Picon, Loret de Mola, in our midst.